Bharatiya nagarik suraksha sanhita, 2023 (criminal procedure) : a commentary - Verma, J. K. (Lucknow : Eastern Book Company, 2024)
"Bharatiya Nagarik Suraksha Sanhita, 2023 (Criminal Procedure): A commentary by J.K. Verma is a treatise on the newly enacted Bharatiya Nagarik Suraksha Sanhita, 2023 (BNSS), which has repealed and replaced the Code of Criminal Procedure, 1973 (CrPC). The BNSS, replacing the CrPC, now comprises 531 sections. Of these, 160 sections of the CrPC have been changed, amended, or substituted. Additionally, 9 new sections have been added, and 9 sections have been repealed. Notable features of the new law include the introduction of e-FIRs, the compulsory recording of the victim?s statement in cases of sexual violence, and the video recording of statements in cases of sexual harassment. The law also mandates regularly furnishing the status of complaints to the complainant, shows enhanced concern for victims, provides for deemed sanction for prosecution, rules out total pardoning, and promotes forensic science to optimise the rate of conviction. The BNSS broadens the scope of police power in property seizure. While the CrPC initially allowed the seizure of movable properties suspected to be stolen or found under suspicious circumstances, Section 85 of the BNSS extends this authority to include immovable properties as well. The prefatory notes by Manisha Karia, Kumar Askand Pandey, and Sanjay Vashishtha, who are prominent criminal law academicians and practitioners, will be quite useful and informative for readers. The book also includes a comparative table showing the correspondence between the provisions of the old law and those of the new law."--
Keywords: India Criminal procedure; Criminal law